A Need Analysis for Curriculum Design of Business English Class in Batam International University - Destrin, Destrin; Zaki, Leil Badrah (Universitas Islam Negeri Raden Intan Lampung, 2020)
The increasing of foreign companies and technologies nowadays, makes many people work in this technology development which must use technologies on their business so that they can connect to other countries to have a partnership in business, that make the people who want to find a job or running a business must have the requirement of English proficiency and ESP must be learned to make the learners easily understand what they want to learn and what they lack in English. This study will be helpful for designing the ESP course to the students based on the needs analysis that filled from the students regarding the students' English score data and skills knowledge that related to the business English.